EFFECT OF VOGLIBOSE ON LIPID PROFILE IN ALLOXAN-INDUCED DIABETIC RABBITS WITH TYPE-II DIABETES MELLITUS AND DYSLIPIDEMIA. - MANAS RANJAN NAIK,; RATNA PALIT,; DIVYA AGRAWAL,; KARMAJEET RATH,; SANJAY KUMAR,; SUDHANSHU S MISHRA, (International Journal of Pharma and Bio Sciences, 2014)
Diabetes is an iceberg disease. There is an increase in the prevalence and incidence of Type-II DM globally. It is an incurable metabolic disorder. Diabetes mellitus always regarded primarily as a disturbance of carbohydrate metabolism. It is the last few decades that the disturbances in lipid metabolism has been described in association with Type II DM. Diabetes is a syndrome characterized by chronic hyperglycemia and disturbance of carbohydrate, lipid, and protein metabolism. There are several reports showing that hyperglycemia and hyperlipidemia are associated with increased cardiovascular risks.Alfaglucosidase inhibitors like acarbose,voglibose and miglitol inhibits the action of enzyme alfaglucosidase and reduces post prandial hyperglycemia on chronic use. As voglibose decreases post prandial hyperglycemia it spares beta cells of the pancrease and decreases the progress of the disease and also decreases insulin resistance.36 rabbits were induced diabetic by administering alloxan I.V. in the marginal ear vein of rabbits. Doses of alloxan required to induce diabetic according to kg body wt of the rabbits as reference table. Voglibose was found to be statistically significant than control group lipid profile at 8thweek of treatment (p<.01).Voglibose an alfaglucosidase inhibitor having beneficial effect on hyperlipidemia associated with hyperglycemia. Voglibose treatment tends to decrease the diabetes induce rise in lipid levels and decrease the risks of coronary heart diseases.These result suggests that,voglibose reduces progression of coronary heart disease along with impaired glucose tolerance stage and may be a candidate for an anti atherosclerotic drug for type II DM with dyslipidemia.